2019
DOI: 10.5114/ceji.2019.87058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selected non-steroidal anti-inflammatory drugs on activation-induced CD25 expression on murine CD4+ and CD8+ T cells: an in vitro study

Abstract: The main aim of this study has been to determine the effect of selected non-steroidal anti-inflammatory drugs (NSAIDs) – depending on their selectivity to cyclooxygenase (COX) 1 and 2 – on the activation-induced CD25 expression on CD4+ and CD8+ T cells. Lymphocytes obtained from lymph nodes of mice were treated with acetylsalicylic acid (ASA; a preferential COX-1 inhibitor), ketoprofen (KET; a non-selective COX inhibitor) and robenacoxib (ROB; a selective COX-2 inhibitor) in concentrations reflecting their pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
(30 reference statements)
1
6
0
1
Order By: Relevance
“…Foxp3, IL-10) expression from both mouse and human effector T cells through direct actions on T cells via EP2 and/or EP4 receptors [32,33,[61][62][63][64]. In agreement with these reports, blocking PG biosynthesis including PGE 2 production by NSAIDs or blocking PGE 2 signalling by an EP4 selective antagonist enhanced Foxp3 expression and iTreg induction, and therefore ameliorated T cell-mediated tissue inflammation [32,[65][66][67]. Moreover, we have recently found that PGE 2 inhibits Treg cell expansion or accumulation in the intestine through T cell-independent but microbiotadependent mechanisms [35].…”
Section: Discussionsupporting
confidence: 59%
“…Foxp3, IL-10) expression from both mouse and human effector T cells through direct actions on T cells via EP2 and/or EP4 receptors [32,33,[61][62][63][64]. In agreement with these reports, blocking PG biosynthesis including PGE 2 production by NSAIDs or blocking PGE 2 signalling by an EP4 selective antagonist enhanced Foxp3 expression and iTreg induction, and therefore ameliorated T cell-mediated tissue inflammation [32,[65][66][67]. Moreover, we have recently found that PGE 2 inhibits Treg cell expansion or accumulation in the intestine through T cell-independent but microbiotadependent mechanisms [35].…”
Section: Discussionsupporting
confidence: 59%
“…PTI is a gene for which there is not a true homolog in humans, coding for a pancreatic trypsin inhibitor, long known for pigs [ 38 ]. In the pancreas, it has a protective action, while in the blood it could have relevance as an antifibrinolytic factor on the homology of the molecule of bovine origin [ 39 ]. Regulation of the activation of PTI has not been studied previously, even though there is increasing interest in medicine regarding this kind of protein.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we also examined CD39 + (T-cell exhaustion marker) (Canale et al, 2018) and CD25 + (T-cell activation marker) immune cells (Gregorczyk & Maslanka, 2019) by flow cytometry analysis. After treatment with anti-IL-6, CD39 + immune cells in Tet2 À/À mice decreased to WT levels, while CD25 + immune cells in Tet2 À/À mice increased to WT levels ( Fig EV5D-G).…”
Section: Il-6 Induces G-mdscs Over Expansion In Tet2 à/à Micementioning
confidence: 99%